FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS HIDUP LANSIA PENDERITA HIPERTENSI DI PUSKESMAS KARET KUNINGAN JAKARTA SELATAN TAHUN 2022 - Theresia Angelin Hulu (2023)
Hypertension is a world health problem that very important to be concerned about because its prevalence continues to increase and due to main cause of death premature in world. According to Riskesdas (2018), the prevalence of hypertension in Indonesia reachs 34,11% and the prevalence of hypertension in Jakarta (2018) reachs 33,43%. Hypertension is major health problem that holds the first position of non-communicable diseases in Karet Kuningan Primary Healthcare Center. According to Primary Healthcare data (2021), the prevalence of hypertension reachs 20,3%. The total number of visits of the elderly with hypertension in 2021 are 1347 visits or 32.37% of total visits of hypertension patients. The population of elderly with hypertension in Karet Kuningan Subdistrict Primary Healthcare are 145 elderly. This study aimed to determine the factors that affect the quality of life in elderly people with hypertension. The type of this research was observational analytic with cross-sectional design. The research sample were 80 samples who eligible to inclusion and exclusion criteria. Primary data was obtained by using the questionnaire and also interviews whereas secondary data using medical records. Data were analyzed using chi-square, fisher, and binary logistic regression. Variables that have a significant relationship with the quality of life respondent are gender, educational, marital status, number of antihypertensive medicine, adherence to antihypertensive medicine, and family support, Marital status is the most dominant factor related to the quality of life in respondent, OR = 35,133. The conclusion of this research is marital status is the most dominant factor related to the quality of life in elderly people with hypertension. Contribution of spouse like providing support, affection, and positive coping for the elderly can help the elderly to live their lives in old age which leads to improve their quality of life